Anti-TNF-α antisense-oligonucleotide-conjugated PLG nanoparticles protect transplanted islets - Elizabeth J. Bealer; Namit Padgaonkar; Kelly Crumley; Eiji Saito; Zoe Beekman; Alexa DeKorte; Thazha P. Prakash; Alexey Revenko; Lonnie D. Shea (Molecular Therapy: Methods & Clinical Development)
One of the many challenges for islet transplantation as a treatment for type 1 diabetes is inflammation that contributes to islet de-differentiation and death. Innate immune cells such as monocytes and macrophages secrete tumor necrosis factor alpha (TNF-α), interleukin 1β (IL-1β), inducible nitric oxide synthase (iNOS), and IL-6, which directly contribute to islet dysfunction. Attenuation of the early inflammatory response post-transplantation may protect cell survival and subsequent function. Herein, we investigate the development of anti-TNF-α antisense-oligonucleotide-conjugated polylactide-co-glycolide nanoparticles (PLG-aTNF-α NPs) as an anti-inflammatory therapy after stem-cell-derived islet transplantation. PLG-aTNF-α NPs are shelf stable and successfully reduce TNF-α secretion and expression in inflammatory macrophages. Synergy between the aTNF-α antisense oligonucleotide and the polylactide-co-glycolide NPs results in further knockdown of IL-1β, IL-6, iNOS, and IL-12 in vitro indicating PLG-aTNF-α NPs may protect against the inflammatory cascade in vivo. In a diabetic mouse model, stem-cell-derived islets transplanted to the peritoneal fat were protected after treatment with PLG-aTNF-α NPs compared with PLG NPs alone. Tnfα and Il1β expression was reduced in mice treated with PLG-aTNF-α NPs, indicating inflammation was reduced after transplant. PLG-aTNF-α NPs reduce TNF-α and protect islets, supporting their potential use as a therapeutic in islet transplantation.